Measuring Responsibility and Cooperation in Learning Teams in the University Setting: Validation of a Questionnaire - León-del-Barco, Benito; Mendo-Lázaro, Santiago; Felipe-Castaño, Elena; Fajardo-Bullón, Fernando; Iglesias-Gallego, Damián (Frontiers in Psychology, 2018)
Cooperative learning are being used increasingly in the university classroom, in order to promote teamwork among students, improve performance and develop interpersonal competences. Responsibility and cooperation are two fundamental pillars of cooperative learning. Team members' responsibility is a necessary condition for the team's success in the assigned tasks. Students must be aware that they depend on each other and should make their maximum effort. On the other hand, in efficient groups, the members cooperate and pool their efforts to achieve the proposed goals. In this research, we propose to create a Questionnaire of Group Responsibility and Cooperation in Learning Teams (CRCG). Participants in this work were 375 students from the Faculty of Teacher Training of the University of Extremadura (Spain). The CRCG has very acceptable psychometric characteristics, good internal consistency and temporal reliability. Moreover, structural equation analysis allowed us to verify that the latent variables in the two factors found are well defined and, therefore, their assessment is adequate. Besides, we found high significant correlations between the Learning Team Potency Questionnaire (CPEA) and the total score and the factors of the CRCG. This tool will evaluate cooperative skills and offer faculty information in order to prepare students for teamwork and conflict resolution.